Assessment of SCC and behaviors of dairy cows fed with Promyxalicin - Factori, Marco Aurélio; Fernandes , Daniela Seko; Costa, Roque Sanchez (Pubvet, 2024)
To improve productivity, dairy producers are increasingly seeking to improve the productive efficiency of the herd. Therefore, the present study was carried out on a private property in the city of Santo Anastácio, in the region of Presidente Prudente/SP (Brazil), characterized by a milk production system in more concentrated pasture, with supplementation of roughage for the animals in the winter months. 16 lactating cows of the Holstein, Girolanda and crossbred breeds (average weight of 480 kg) were used. The objective of this work was to evaluate the effect of adding Promixalicin to the diet on the behavior of lactating cows, and on the SCC (Somatic Cell Count) of the animals’ milk. The animals were analyzed for 180 days, but Promyxalicin was supplied from the 61st to the 120th experimental day. Animal behavior was observed in relation to head and tail shaking, and animal restlessness due to attacks by ectoparasites (Haematobia irritans, Stomoxys calcitrans and ticks). Monthly SCC measurements were taken of the animals’ milk in the first week of each month, throughout the experimental period. It can be inferred that, on the day the Promyxalicin supply began (day 61), the animals showed many stress behaviors such as tail wagging, head shaking and restlessness. Its benefits were significant from the 7th day after using the product (67th day), implying its efficiency for the evaluation of ticks on animals. 15 days after the start of supplying the product (75th experimental day), there was a significant reduction in the number of ticks remaining on the animals. Regarding SCC, the use of Promyxalicin proved to be effective as it significantly improved the animals’ SCC within just 30 days of using the product. The use of Promyxalicin for lactating cows improved animal well-being due to the repellence of ectoparasites, and significantly reducing the SCC of the milk, indicating an improvement in animal performance, mainly due to the improvement of conditions for increased milk production.